Rancang Bangun Vending Machine Penukar Uang Koin Berbasis Mikrokontroller - Firdaus Firdaus; Muhammad Irmansyah; Dikky Chandra; Era Madona (Prosiding SISFOTEK, 2018)
Vending machine money changer is made to help stalls, mini market or bank to exchange money and making easier exchange money to coins. This device based on Arduino Uno microcontroller to control the device. This tool uses TCS3200 color sensor to detect color of Rp 5,000, dc motor to withdraw money and servo motor to eject coin Rp 1,000. In this device LCD is used to view how to use vending machine and the amount of coins out.